Platelet counting using the Coulter electronic counter. Issue 2 (March 1963) - Eggleton, M. J.; Sharp, A. A.
Abstract : A method for counting platelets in dilutions of platelet-rich plasm using the Coulter electronic counter is described. 1 The results obtained show that such platelet counts are at least as accurate as the best methods of visual counting. The various technical difficulties encountered are discussed.